(untitled) (Research, Society and Development, 2025)
The World Health Organization (WHO) classifies incidents involving venomous animals as neglected tropical diseases. This study provides a descriptive and retrospective epidemiological and clinical analysis of snakebite accidents recorded in the municipality of Castanhal between January 2019 and December 2023. The aim is to assess the incidence and clinical characteristics of reported cases. The data was obtained from the Department of Informatics of the Unified Health System (DATASUS). During this period, there were 608 snakebite notifications, resulting in three deaths (0.49%). Most of the cases occurred in Castanhal (39.80%), with significant numbers also in Terra Alta (8.39%) and São Francisco (8.06%). Men were the most frequently affected (75.82%) and the predominant age group was between 20 and 39 years old (35.36%). The year 2021 had the highest incidence of accidents (24.84%), with the months of January, February and March standing out, coinciding with the rainiest period in the state of Pará. Serotherapy was used in 94.24% of cases. The high rate of snake accidents in the region represents a concern for public health, making it crucial to conduct research and implement awareness and control initiatives in order to prevent new cases.